A unified model for estimating and testing familial aggregation. (21st October 2013) - Lee, Myeongjee; Rebora, Paola; Valsecchi, Maria Grazia; Czene, Kamila; Reilly, Marie; Aalen, Odd O.; Borgan, Ørnulf; Kvaløy, Jan Terje
<x xml:space="preserve">Abstract</x> Investigations of familial aggregation of disease can provide important clues for genetic mechanisms, and many such studies have been published in the epidemiological literature using various statistical methods. We developed a unified model for familial risk by extending a Cox regression model to enable estimation of the detailed effects of kinship. By appropriate parameterisation of the model, we show how the risks to all specific first‐degree kinships can be estimated and formally compared using simple interaction terms and how the model can be extended to accommodate higher‐degree relatives. The correlation due to observations from family members and from the potential for repeated observations is accommodated by a robust sandwich variance estimator or a bootstrap estimate. Hazard ratios for different kinships are formally compared using a robust Wald test. We illustrate the method with applications to studies of adult leukemia and non‐Hodgkin's lymphoma in the Swedish population and display our results on a pedigree diagram. Our estimates are consistent with published work that used simpler stratified methods, and our model enabled the detection of a number of statistically significant effects of kinship. The recognition of such kindred‐specific disease risk could be a first step in the design of more informative genetic biomarker studies. Copyright © 2013 John Wiley & Sons, Ltd.